PÅ GYNGENDE GRUND: Udfordringer ved den multilokale forskningsmetode - Jakobsen, Turf Böcker (Tidsskriftet Antropologi, 2005)
George E. Marcus has introduced the notion of a multi-sited ethnography as an attempt to deal methodologically and analytically with anthropological fieldwork in a postmodern era. This article discusses some of the crucial challenges of this approach. Particular attention is paid to the various ‘tracking strategies’ suggested by Marcus, e.g. “following the conflict”. A study of an institutional complex of complaint boards, established to secure the legal rights of social clients in Denmark, works as an empirical illustration. It is shown how the idea of “following the conflict” helped to organise the research process. However, this tracking strategy contained some difficulties of its own, and the principle of multi-locality highlighted unexpected aspects of the “conflicts” between state and citizen. This prompts reflection upon the sort of knowledge than can be gained from doing ethnographic fieldwork. The article concludes by suggesting multi-sited ethnography as an important and promising tool in anthropological research. Most importantly, it helps the ethnographer to consider and handle the unpredictability of fieldwork in a structured and yet flexible manner.